MO647RENOPROTECTIVE EFFECT OF SGLT2 INHIBITORS AFTER FIVE YEARS OF TREATMENT: AN OBSERVATIONAL STUDY. (29th May 2021) - Almeida, Catarina; Silva, Leonor; Costa, Tiago; Lopes, Daniela; Faria, Victoria; Suarez, Elena; Veríssimo, Rafaela; Caçola, Rute; Gil, Pedro; Andrade, Luís
Abstract: Background and Aims: Sodium-glucose co-transporter 2 (SGLT2) inhibitors, the most recent glucose lowering oral agents, prevent glucose and sodium reabsorption at proximal tubules. These drugs have the potential of nephroprotection by their glucose lowering effects, but also through direct renal effects, such as reducing intraglomerular pressure and suppressing the production of pro-inflammatory and pro-fibrotic factors. Several randomized control trials have demonstrated these effects with slowing chronic kidney disease progression. The aim of our study was to evaluate the effect of SGLT2 inhibitors on estimated glomerular filtration rate throughout five years of treatment. Method: This was a retrospective observational and longitudinal study that included patients diagnosed with DM2 and treated with an iSGLT2 in a Diabetic Clinic. Demographic and clinical variables were collected, including HbA1c, disease duration and cardiovascular risk factors (CVRF). Patient glucose-control therapy as well as RAAS inhibitor drugs were gathered. The estimated Glomerular Filtration Rate (eGFR) by the formula CKD-EPI and albuminuria, using the urinary albumin-to-creatinine ratio, were evaluated at the iSGLT2 introduction date and at 6, 12, 24, 36, 48 and 60 months of treatment. Categorical variables are presented as frequencies and percentages, and continuous variables as means or medians for variables with skewed distributions. All reported p values are two-tailed, with a p value of 0.05 indicating statistical significance. A paired Student's t-test or paired-sample test were performed for continuous variables and a chi-squared test was performed for categorical variables. Results: A total of 205 patients, 54, 6 % male, mean age 65, 4 years, median baseline HbA1c 8, 4% and median duration of DM2 14 years were studied. Of all patients, 94, 1% had at least 1 CVRF, 71, 2% hypertensive, 83, 4% dyslipidemia, 48, 8% obese, and 25, 4% had past/current smoking habits. Regarding glucose-control therapy 17, 1% were treated with one drug class and the remaining patients were treated with 2 or more classes. Among the patients 82, 0% of them were taking metformin and 51, 2% were on insulin therapy. Also, 56, 6 % were on a RAAS inhibitor. Overall, 129 (62, 9 %) patients received dapaglifozin therapy (5 or 10mg) and 76 (37, 1%) empaglifozin (10 or 25mg). Regarding albuminuria at baseline, 37 patients had normal albuminuria (<30mg/g), 18 patients had moderate albuminuria (30-300mg/g) and 6 patients had severe albuminuria (>300mg/g). As for eGFR, 15, 6 % patients had an eGFR between 30 and 60 and 84, 4% patients had an eGFR greater than 60 ml/min/1, 73m2. These clinical features were similar between the patients that received either SGLT2 inhibitor, with the exception of obesity being more prevalent in the dapaglifozin group (55, 8 % vs 36, 8%, p=0, 009). Assessing the eGFR during the 5 years of treatment, a significant decrease was noticed in the first 6 months from an 82, 3 to 78, 6 ml/min/1, 73m2 (p=0, 002), followed by a significant increase in the second semester to 82, 9 ml/min/1, 73m2 (p<0, 001). Thereafter there is a slight increase in eGFR throughout the years, to a maximum of 84, 1 ml/min/1, 73m2 at 24 months and after a slow reduction to 80, 6ml/min/1, 73m2 in the end of the 5 years of SGLT2 inhibitor use. Conclusion: This observational study shows that after an initial reduction in eGFR during the first 6 months of treatment, the use of iSGLT2 after five years slowed the decrease in eGFR, similar to what randomized control trials have demonstrated, promoting a renoprotective effect on type 2 diabetic patients.